Studi Literatur: Menelusuri Model-Model Pembelajaran yang Efektif Untuk Meningkatkan Kemampuan Berpikir Komputasi Siswa - Farizi Aqfi; Yahfizham Yahfizham (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2024)
The importance of computational thinking skills has encouraged educational institutions around the world to integrate these concepts into their curricula. However, the challenge faced is finding the most effective learning methods and models to teach these skills. An appropriate learning model must not only be able to attract students' interest and motivation, but must also be able to increase their understanding and practical abilities in computational thinking. This research adopts a literature review method to explore information about effective learning models in improving students' computational thinking skills. Data was collected from various sources such as national and international journals, reference books, newspapers and magazines. The main aim of this literature review, as explained. The results of research on Problem Based Learning (PBL) and Project Based Learning show very positive results in improving students' computational thinking. These two models not only improve computational thinking skills, but also critical, creative and analytical thinking skills, as well as student participation and involvement in the learning process.